Dysregulation of miR-31 and miR-21 induced by zinc deficiency promotes esophageal cancer - Alder, Hansjuerg (Oxford University Press, 2012)
Zinc deficiency (ZD) increases the risk of esophageal squamous cell carcinoma (ESCC). In a rat model, chronic ZD induces an inflammatory gene signature that fuels ESCC development. microRNAs regulate gene expression and are aberrantly expressed in cancers. Here we investigated whether chronic ZD (23 weeks) also induces a protumorigenic microRNA signature. Using the nanoString technology, we evaluated microRNA profiles in ZD esophagus and six additional tissues (skin, lung, pancreas, liver, prostate and peripheral blood mononuclear cells [PBMC]). ZD caused overexpression of inflammation genes and altered microRNA expression across all tissues analyzed, predictive of disease development. Importantly, the inflammatory ZD esophagus had a distinct microRNA signature resembling human ESCC or tongue SCC miRNAomes with miR-31 and miR-21 as the top-up-regulated species. Circulating miR-31 was also the top-up-regulated species in PBMCs. In ZD esophagus and tongue, oncogenic miR-31 and miR-21 overexpression was accompanied by down-regulation of their respective tumor-suppressor targets PPP2R2A and PDCD4. Importantly, esophageal miR-31 and miR-21 levels were directly associated with the appearance of ESCC in ZD rats, as compared with their cancer-free Zn-sufficient or Zn-replenished counterparts. In situ hybridization analysis in rat and human tongue SCCs localized miR-31 to tumor cells and miR-21 to stromal cells. In regressing tongue SCCs from Zn-supplemented rats, miR-31 and miR-21 expression was concomitantly reduced, establishing their responsiveness to Zn therapy. A search for putative microRNA targets revealed a bias toward genes in inflammatory pathways. Our finding that ZD causes miR-31 and miR-21 dysregulation associated with inflammation provides insight into mechanisms whereby ZD promotes ESCC.